THE MANAGEMENT OF A TRAINING DEVELOPMENT STRATEGIES TO INCREASE THE COMPETITIVE ADVANTAGE OF LIFE LOCAL INSURANCE COMPANIES - Tirto Utomo, Jazai; Ruslan, Sangkala (Dinasti International Journal of Management Science, 2021)
This study aims to analyze the development of training management for employees and agents as well as a training roadmap model and human resource development in increasing competitive advantage in Local Life Insurance. The paradigm in the implementation of this research uses a qualitative phenomenological paradigm as a reference, pattern and framework that starts from empirical generalizations or empirical generalizations on the growth and development of social reality. ThisXresearchxuses qualitativexmethods with thextype ofXcaseXstudy research. Primary data were obtained from information and factual experiences of informants using structured interviews through In-depth interviews and focus group discussions. The results of the study found that this local life insurance company did not yet have training management and employee development. HRD is not able to formulate employee development patterns. This company needs to conduct a comprehensive evaluation of the occurrence of a vacancy in the management system for employee training and development. The results of the study also show management's neglect when there is a vacancy of the people development function by the company's HRD. Agency Training & Development already owns and implements Agent training management